Oblicz
c)(-6,5)³/(-0,13)³
d)(4½)³×(-⅔)³×(-2)³
b)(-½)³×(-½)⁴×2⁷
a)0,1⁸×0,2⁸÷0,02₆
c)=
d)=
b)=
a)=
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
c)=![(-6,5:(-0,13))^3=50^3=125000 (-6,5:(-0,13))^3=50^3=125000](https://tex.z-dn.net/?f=%28-6%2C5%3A%28-0%2C13%29%29%5E3%3D50%5E3%3D125000)
d)=![(4\frac{1}{2}*(-\frac{2}{3}*(-2))^3=(\frac{9}{2}*(-\frac{2}{3})*(-2))^3=6^3=216 (4\frac{1}{2}*(-\frac{2}{3}*(-2))^3=(\frac{9}{2}*(-\frac{2}{3})*(-2))^3=6^3=216](https://tex.z-dn.net/?f=%284%5Cfrac%7B1%7D%7B2%7D%2A%28-%5Cfrac%7B2%7D%7B3%7D%2A%28-2%29%29%5E3%3D%28%5Cfrac%7B9%7D%7B2%7D%2A%28-%5Cfrac%7B2%7D%7B3%7D%29%2A%28-2%29%29%5E3%3D6%5E3%3D216)
b)=![(-\frac{1}{2})^{3+4}*2^7=(-\frac{1}{2})^7*2^7=(-\frac{1}{2}*2)^7=-1^7=-1 (-\frac{1}{2})^{3+4}*2^7=(-\frac{1}{2})^7*2^7=(-\frac{1}{2}*2)^7=-1^7=-1](https://tex.z-dn.net/?f=%28-%5Cfrac%7B1%7D%7B2%7D%29%5E%7B3%2B4%7D%2A2%5E7%3D%28-%5Cfrac%7B1%7D%7B2%7D%29%5E7%2A2%5E7%3D%28-%5Cfrac%7B1%7D%7B2%7D%2A2%29%5E7%3D-1%5E7%3D-1)
a)=![(0,1*0,2)^8:0,02^6=0,02^8:0,02^6=0,02^{8-6}=0,02^2=0,0004 (0,1*0,2)^8:0,02^6=0,02^8:0,02^6=0,02^{8-6}=0,02^2=0,0004](https://tex.z-dn.net/?f=%280%2C1%2A0%2C2%29%5E8%3A0%2C02%5E6%3D0%2C02%5E8%3A0%2C02%5E6%3D0%2C02%5E%7B8-6%7D%3D0%2C02%5E2%3D0%2C0004)